Imatinib mesylate – tyrosine kinase inhibitor in the treatment of gastrointestinal stromal tumors (GIST) - Nasierowska-Guttmejer, Anna; Rutkowski, Piotr; Grzesiakowska, Urszula; Ruka, Włodzimierz; Nowecki, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2002)
Gastrointestinal stromal tumors (GIST) comprise a group of sarcomas of the gastrointestinal tract at high risk of recurrence and resistance to chemotherapy. The presence of membrane receptor CD-117 (c-KIT protooncogene) in the GIST cells indicates their origin from cells of Cajal. The diagnosis of these tumours is difficult and treatment results unsatisfactory. Results of phase III and IV of clinical trials on the usefulness of the new molecular targeting drug -imatinib - tyrosine kinases inhibitor in treatment of inoperative GISTs show its effectiveness. The paper describes current clinical experience in the treatment of GIST patients with imatinib. The introduction of imatinib to the therapy has markedly altered the clinical approach to GIST. High percentage of patients (77-93%) in all clinical trials is still alive and is treated with imatinib, which implies at least the stop of the progression of the disease. However, with longer follow-up time, the resistance to imatinib is increasing. Imatinib in doses of 400-800 mg demonstrates low toxicity, including mainly edema and anemia. The unsolved clinical problems in GIST patients treated with imatinib are presented: diagnostic criteria of GIST, assessment of the response to imatinib, the period of time of treatment with imatinib, the combination of surgical resection with imatinib. The authors suggest organizing nation-wide health program, in cooperation with interested parties, to ensure access to this expensive treatment for all eligible patients and to collect necessary pathological and clinical data to address present and future problems connected with GIST diagnosis and treatment.